2003
DOI: 10.1159/000081512
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Hemostatic Markers and Circulating Biochemical Markers of Collagen Metabolism in Patients with Aortic Aneurysm

Abstract: Our objective was to determine the relationship between plasma levels of hemostatic molecular markers – D-dimer and thrombin-antithrombin III complex (TAT) – and circulating biochemical markers of collagen metabolism – aminoterminal propeptide of type III procollagen (PIIIP) and carboxyterminal propeptide of type I procollagen (PICP) – in patients with aortic aneurysm. The subjects were 43 patients with aortic aneurysm (AA; mean age 71 years) and 26 age-matched controls (mean age 75 years). The mean D-dimer, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
(14 reference statements)
1
11
0
3
Order By: Relevance
“…D-dimer has been correlated with collagen markers in conditions such as aortic aneurysms [29]; hence, our results suggest a relation between collagen metabolism and the general fibrinolytic system, with a stronger relation seen with the plasminogen/plasmin system.…”
Section: Discussionmentioning
confidence: 56%
“…D-dimer has been correlated with collagen markers in conditions such as aortic aneurysms [29]; hence, our results suggest a relation between collagen metabolism and the general fibrinolytic system, with a stronger relation seen with the plasminogen/plasmin system.…”
Section: Discussionmentioning
confidence: 56%
“…Increased larger platelets in AC of the present study might possibly be a result of age-related atherosclerosis, possibly entailing chronic platelet consumption at the site of the atherosclerotic plaque. Thrombus formation is generally strong in patients with AA, as refl ected by elevated D-dimer and TAT [14,15] , especially in group B. The increase in platelet size was accompanied by a decrease in platelet count, and the life span of 'stress' platelets will be remarkably shortened and thus, as a compensatory response, thrombopoiesis may be strongly accelerated leading to the formation of lager platelets.…”
Section: Discussionmentioning
confidence: 99%
“…57 Thus, PF1 ϩ 2 and TAT are biomarkers of coagulation activation and thrombin generation. This review identified eight studies that reported on the effect of AAAs on the levels of one or both of these biomarkers [41][42][43]45,47,[50][51][52] ( Table II). Elevated levels of both TAT and PF1 ϩ 2 have been demonstrated in men with small AAAs Ͻ55 mm in diameter.…”
Section: Reported An Independent Association Betweenmentioning
confidence: 99%